MODERN LEGAL DEFINITION OF HUMAN HEALTH - Mazure, Līga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The World Health Organisation has proposed an innovative view on the legal definition of human health, which countries have borrowed and included in their national laws and regulations. At the beginning the legal definition of human health was seen as an innovation and a progressive view on the legal understanding of human health. However, nowadays this legal definition of human health is considered too narrow and needs to be specified in two areas. Firstly, the legal definition of human health should include significant and already existing health principles for objective and comprehensive interpretation. Secondly, nowadays, a more detailed evaluation of the notion of health broadens its interpretation, revealing new aspects of the definition of human health.The research aim is to analyse the legal definition of human health and propose its more specific version in accordance with the modern legal system. The following main research methods of the legal science were used: analytical, systemic, teleological.